Prediction of an Optimum Total Resistance Coefficient on Catamaran using Design of Experiment (DOE) Incorporated with CFD Approach - Ahmad Fitriadhy; Sun Yin Lim; Adi Maimun (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
In presence of complex hydrodynamic interferences between two demihulls on a catamaran ship has been prone to have a reliable prediction to her optimum total resistance. To achieve this, the author presents a Computational Fluid Dynamic (CFD) modelling incorporated with Design of Experiment (DOE) approach. Several parameters such as effect of Froude number ( ) with respect to various lateral separation ratios (S/L) of the catamaran have been taken into account. Here, the optimum total resistance coefficient (CT) has been mainly set within the range of S/L ratio 0.2 ≤ S/L ≤ 0.4 associated with Froude number 0.56 ≤ ≤ 0.66. The primary objective function of this optimization model has led towards minimizing a drag force and increased a lift force with respect to the above S/L ratios. In general, the simulation results had seemed quantitative similarity values for the optimum of 0.6589, 0.6599 and 0.6596 with S/L ratios of 0.2, 0.3 and 0.4, respectively. In the case of = 0.56, the optimum S/L ratios of 0.2993 and 0.3988 have resulted in insignificant reduction of CT by 0.62% and 0.32% as compared to S/L of 0.3 and 0.4, respectively. Similarly, the optimum S/L ratios of 0.2750 and 0.3750 with = 0.66 have led to reduce by 0.14% and 0.46% as compared to S/L of 0.3 and 0.4, respectively. This CFD simulation results are very useful as preliminary data for the optimised ship resistance, which is mainly required to predict a ship powering in the early design stage.